Uji Efektivitas Ekstrak Buah Bengkuang (Pachyrhizus erosus (L.) Urb.) Sebagai Pengawet Alami Cabai Merah (Capsicum annuum L) - Citra Larasari; Baharuddin Hamzah; Suherman Suherman (Jurnal Akademika Kimia, 2016)
Red chili is one of the food susceptible to decay. It caused by its high water content and so it causes to keep power of red chili abbreviated. Jicama (pachyrizuserosus (L.) Urb.) can act as a natural preservative for red chili due to the saponin compounds contained there in. This study aimed to prove the use of jicama extract as a natural preservative for red chili and to determine the most effective concentration of jicama extract as a natural preservative. The methods used in this study were a maceration to prepare the extract of jicama, and an iodimetric titration to determine the levels of vitamin C before and after curing. The results showed that jicama extract can be used as a natural preservative for red chili. The most effective concentration of jicama extract in preserving the red chili was 4% with preservation durability of red chili for 14 days in which the smallest level of vitamin C decreased among other concentrations, i.e. from 84.47 mg/100 g to 75.13 mg/100 g of material.